Intermediate zones of culture. Reflections on the (historiographical) problem of contemporaneity (Andamios, Revista de Investigación Social, 2016)
This paper addresses the historiographical complexity implied in the analysis of contemporary phenomena from our own temporal and spatial contemporaneity. Particularly, the paper examines new media art practices, which are situated between the evasive instant of the present and the past that is continuously being left behind. As a result, new media art has turned into an in-between zone, since it surpasses the boundaries imposed by “guardians of frontiers” and “historians with time phobia”. After inspecting eight philosophical notions referred to the untimely occurrences that interrupt the continuum of the history, the article concludes by stating that the extemporaneity embodied by those in-between zones is paradoxically the most suitable strategy to tackle contemporaneity.
Keywords: Contemporaneity; extemporaneity; historiography; in-between zones; new media art